The Rolling Stones [videorecording (DVD)] : Havana moon. - Dugdale, Paul (Director) (Eagle Vision, 2016)
Havana moon captures the historic, once in a lifetime concert by The Rolling Stones in Havana, Cuba. This epic, record breaking concert features hits from across their career. Filmed at the end of the América Latina Olé Tour 2016 Mike Jagger, Keith Richards, Charlie Watts, and Ronnie Wood perform a truly spectacular set to over 1.2 million adoring fans.